EVALUASI KINERJA STRUKTUR DUAL SYSTEM DENGAN BELT TRUSS - Utomo, Dwi Prasetyo; Soegiarso, Roesdiman (Universitas Tarumanagara, 2021)
In structural engineering applications, the limit of building deflection or interstory drift is an important issue. In high-rise buildings that are more than or equal to 60 floors in the current era, systems are used in the structure of the building. The function of the Belt Truss is to reduce the deflection that occurs in the building by converting the building's overturning moment into the axial force of the exterior column. The Belt Truss structure itself can use reinforced concrete structures and steel structures. Because the Belt Truss structure is an innovation in the world of structural engineering, the parameter values for earthquake loads are not listed in the applicable Building Planning Standards. The standard for earthquake-resistant building regulations requires the parameters of Response Modification Factor (R), Overstrength Factor (Ωo), and Deflection Magnification (Cd) for determining earthquake loads. Because the parameters on the Belt Truss structure are not listed in the Standard for Earthquake Resistant Building Regulations, a study of the earthquake load parameters on the Belt Truss structure was carried out. The method used in this research is a literature study using Pushover Load Analysis according to ATC - 40 and FEMA 356. Keywords: Belt Truss, Dual System; ATC – 40; FEMA 356; Response Modification Factor (R); Overstrength Factor (Ωo); and Deflection Magnification (Cd) AbstrakDalam aplikasi rekayasa struktur gedung, batasan defleksi bangunan atau interstory drift adalah masalah penting. Pada bangunan tinggi yang lebih dari atau sama dengan 60 lantai pada era sekarang sudah menggunakan sistem pada struktur bangunan tersebut. Fungsi dari Belt Truss tersebut berguna untuk mengurangi defleksi yang terjadi pada bangunan dengan mengkonvesi momen guling bangunan menjadi gaya aksial kolom eksterior. Struktur Belt Truss sendiri materialnya bisa menggunakan struktur beton bertulang dan struktur baja. Karena struktur Belt Truss merupakan inovasi pada dunia rekayasa struktur, maka nilai parameter beban gempa tidak tercantum pada Standar Peraturan Perencanaan Bangunan yang berlaku. Standart Peraturan Bangunan tahan gempa diperlukan parameter – parameter Faktor Modifikasi Respon (R), Faktor Kuat Lebih (Ωo), dan Perbesaran Defleksi (Cd) untuk penentuan beban gempa. Dikarenakan parameter pada struktur Belt Truss tidak tercantum pada Standar Peraturan Bangunan Tahan Gempa, maka dilakukan penelitian parameter-parameter beban gempa pada struktur Belt Truss tersebut. Metode yang digunakan dalam penelitian ini adalah studi literatur dengan menggunakan analisa Beban Dorong Pushover Analysis sesuai ATC - 40 dan FEMA 356.